Change in mode shape nodes of multiple cracked bar: I. The theoretical study - Khiem, Nguyen Tien; Toan, Le Khanh; Khue, Nguyen Thi Linh (Vietnam Journal of Mechanics, 2013)
In present paper change in position of mode shape nodes induced by multiple cracks in bar is studied with purpose to use for the multiple crack detection from measured mode shape nodes. First, there is derived an explicit expression for natural modes in axial vibration of multiple cracked bar that allows obtaining exact positions of the node in the case of single and double crack. The change in mode shape nodes induced by multiple cracks provides an important indicator for crack localization in bar. Finally, a procedure for multiple crack detection by using mode shape nodes has been proposed and examined in an example of application.